GEOLOGICAL STRUCTURE OF THE WIDER AREA OF AEGIALIA AND KALAVRYTA (NORTH PELOPONNESUS) - Τρίκολας Κ.; Αλεξούλη-Λειβαδίτη A. (Bulletin of the Geological Society of Greece, 2004)
The alpine nappe sequence of the wider area of Aegialia and Kalavryta (Aegion sheet) is comprised of 3 alpine units, which from the lower to the upper are: (i) Arna unit, which consists of phyllites and quartzite series, (ii) Tripolis unit that consists of Tyros beds, neritic carbonate sequence and flysch and (iii) Pindos, unit which is represented with all its formations from the Triassic clastic formation at the bottom up to the Eocene flysch at the top. Pindos unit is intensively folded and tectonized forming successive thrusts with direction from east to west. The post alpine deposits are distinguished to (i) fluvial, (ii) fluvial-lacustrine, (iii) lacustrine, (iv) fan delta and (v) marine formations. The lacustrine and the fluvial formations outcrop at the south, central and eastern part of the study area, whereas the fluvial-lacustrine formations, the fan delta deposits and the marine deposits outcrop at the northern part. In the study area normal listric and oblique slip faults of great length have been observed striking WNW-ESE and NW-SE. Also, normal, oblique-slip and strike-slip faults have been observed striking NE-SWto N-S, which were which are younger than the former ones (WNWESE). The tectonic structure of the study area is characterized by the presence of horsts, grabens and blocks, which have been tilted towards SE, and S.